ANALISIS PERBANDINGAN KINERJA PT. BPRS PUDUARTA INSANI DAN PT. BPRS AMANAH INSAN CITA DITINJAU DARI MAQASHID SHARIA INDEX - Adinda Fakhrunnisa; Sudirman Suparmin (Universitas Islam Negeri Sumatera Utara, 2017)
The research was aimed to analyse the comparison of performance between PT. BPRS Puduarta Insani and PT. BPRS Amanah Insan Cita based on maqashid sharia index. The type of this research is descriptive quantitative approach with secondary data, which obtained from the annual report of PT. BPRS Puduarta Insani and PT. BPRS Amanah Insan Cita in 2012-2016. This research used SAW (The Simple Additive Weighting) analyse techniques with MADM (Multiple Attribute Desicion Making). The result of this researh showed that PT. BPRS Amanah Insan Cita does not implement all of the indicators of maqashid sharia index. The value of maqashid sharia index that achieved of PT. BPRS Puduarta Insani and PT. BPRS Amanah Insan Cita is fluctuate. PT. BPRS Amanah Insan Cita is more better in implement the maqashid sharia index as a measure of company performance.